Longitudinal Analysis of Physical Performance, Functional Status, Physical Activity, and Mood in Relation to Executive Function Among Older Fallers - Best, John R. (J Am Geriatr Soc, 2015)
BACKGROUND: Older fallers are at risk of experiencing functional decline within 1 to 3 years; however, not all older fallers show near-term decline. Executive function (EF), which refers to the cognitive processes important for goal-oriented and controlled behavior, may be one factor that underlies resiliency against decline. OBJECTIVES: To examine whether good EF at baseline and maintenance of EF over time predict maintenance of physical performance, functional status, physical activity, and mood over a one-year period. Conversely, to examine whether baseline functioning in these non-cognitive domains predicts maintenance of EF over the same period of time. DESIGN: 12-month prospective cohort study. SETTING: Vancouver Falls Prevention Clinic. PARTICIPANTS: Community-dwelling older adults (N = 199; mean age = 81.6; 63% female) referred to the clinic after suffering a fall. MEASURMENTS: At each time point, structural equation modeling created a latent EF variable from performance on five EF tasks. Physical performance (physiological falls risk and gait speed), instrumental activities of daily living (IADLs), physical activity, and depressive symptoms were also assessed at each time point. RESULTS: Higher baseline EF predicted decreases in depressive symptoms and maintenance of IADLs from baseline to follow-up (p<.01). Improvements in EF correlated with increases in gait speed and physical activity, and with the maintenance of IADLs over the follow-up (p<.05). All effects were independent of demographic characteristics and global cognitive function. Baseline performance in the non-cognitive domains did not predict changes in EF. CONCLUSION: Among older fallers, EF is a marker for resiliency in several non-cognitive domains, and therefore, should be assessed. Furthermore, interventions to improve EF should be tested among older fallers with EF deficits.